Measures of Time of Literature. Review of Rafał Pokrywka’s book titled „Współczesna powieść niemieckojęzyczna”, Universitas, Kraków 2018 - Szymańska, Katarzyna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The article is a discussion of a study by Rafał Pokrywka titled Współczesna powieść niemieckojęzyczna (Kraków 2018). The author of the study analysed selected works written at the turn of the 21st century, and – in an interesting manner – developed his discussion around a progression of three dimensions of time: the past, the present, and the future, which constitute the contexts for reading individual narratives. The interpretations of German, Austrian, and Swiss novels, both these which exist as Polish translations and these which have not yet been translated, are accompanied by cultural and sociological contexts, while the (re)definitions of the words used in the title of Pokrywka’s volume presented in the introduction enable one to place this original overview in the context of modern studies on the most recent literature.